Social Competence of Secondary Schools Adolescents - Šniras, Šarūnas (Pedagogika, 2013)
Indicator of social competence of secondary schools adolescent boys and girls aged 15–16 is analyzed in the article. The aim of the investigation is to reveal the level of the indicators of social competence of adolescents aged 15–16 according to their sex. Social competence of secondary schools adolescents aged 15–16 is the object study. 371 adolescents (192 girls and 179 boys) aged 15–16 from secondary schools participated in the study. The results of the research that evaluation of boys and girls from secondary schools according to some level of indicators is different. While comparing distribution of different groups of boys and girls according to the level of indicator of social competence statistically reliable difference was revealed: according to general trust (χ²(2) = 8.76; p < 0.05), resistance to failure and criticism (χ²(2) = 7.57; p < 0.05), ability to express feelings (χ²(2) = 6.84; p < 0.05), ability to ash for help (χ²(2) = 9.08; p < 0.05). The results showed that adolescents boys of secondary schools have a higher level of indicators of general self-confidence (p <0.05), resistance to failure and criticism (p < 0.05) than girls. It was revealed that girls and disposed to express then feelings (p < 0.05) and are able to ask for help more often (p < 0.05) than boys. However evaluation of secondary schools boys and girls statistically reliably was not different according to such indicators of social competence as uncompromise (p > 0.05), ability to demand (p >0.05), not to feel guilty (p > 0.05).